A CCO-based Sigma-Delta ADC - Ferreira, Bruno Miguel Rosa (2019)
Analog-to-digital converter (ADC) is one of the most important blocks in nowadays systems. Most of the data processing is done in the digital domain however, the physical world is analog. ADCs make the bridge between analog and digital domain. The constant and unstoppable evolution of the technology makes the dimensions of the transistors smaller and smaller, and the classical solutions of Sigma-Delta converters (ΣΔ) are becoming more challenging to design because they normally require high active gain blocks difficult to achieve in modern technologies. In recent years, the use of voltage-controlled oscillators (VCO) in ΣΔ converters has been widely explored, since they are used as quantizers and their implementations are mostly made with digital blocks, which is preferable with new technologies. In this work a second-order ΣΔ modulator based on two current-controlled oscillators (CCO) with a single output phase and an independent phase generator for each CCO that generates any desired number of phases using the oscillation of its CCO as reference has been proposed. This ΣΔ modulator was studied through a MATLAB/Simulink® model, obtaining promising results with the SNDR in the order of 75 dB, at a sampling frequency of 1 GHz, and a bandwidth of 5 MHz, corresponding to an ENOB of, approximately, 12 bits.